Development of History Teaching Materials in the Form of Booklets on the Proclamation of Indonesian Independence Materials to Increase the Learning Interest of Grade XI Students of SMAN 1 Kertek Wonosobo - Ningrum, Anna Fitri; Jayusman, Jayusman; Amin, Syaiful (Indonesian Journal of History Education, 2020)
The research objectives are: (1) To produce and analyze history teaching material in a booklet of Indonesia’s Independence Proclamation, which will be developed in SMA N 1 Kertek. (2) To know and analyze the feasibility of history teaching material in the form of a booklet on Indonesia’s Independence Proclamation from the validation results of material and media experts, practitioners, and students' responses. (3) To describe the effectiveness of using history teaching material in the form of a booklet of Indonesia’s Independence Proclamation seen from the average student’s learning interest in SMA N 1 Kertek. The type of research conducted is Research and Development (R&D), which is grouped into three stages: introduction, development, and evaluation. The approach used by the researcher is a quasi-experimental approach, which is a nonequivalent control group design. The results show (1) the Condition of teaching material developed based on interviews and analysis of teaching materials needs. (2) The development of teaching material in the form of a developed booklet is considered feasible based on the validation results by the experts (3) History teaching material in the form of a booklet Indonesia’s Independence Proclamation is effective to be applied in learning History of Indonesia in SMA N 1 Kertek.